Multimodal biometrics and intelligent image processing for security systems - Gavrilova, Marina L.; Monwar, Maruf (Premier reference source, 2013)
"This book provides an in-depth description of existing and fresh fusion approaches for multimodal biometric systems, covering relevant topics affecting the security and intelligent industries" - Provided by publisher